2018
DOI: 10.1002/jor.24067
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of tendon rupture depends on strain rate and tendon type

Abstract: Previous research has shown that both the mechanics and elongation mechanisms of tendon and ligament vary with strain rate during tensile loading. In this study, we sought to determine if the ultrastructural damage created during tendon rupture also varies with strain rate. A bovine forelimb model was used, allowing two anatomically proximate but physiologically distinct tendons to be studies: the positional common digital extensor tendon, and the energy storing superficial digital flexor tendon. Samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Very different values were registered compared to those found in literature, due to the different preconditioning and strain rates applied in this study from other literature [ 31 ]. Tendons had a viscoelastic behavior for which a strong test parameter dependence exists: an increase in the stress and strain at failure was registered with a strain rate increase [ 32 , 33 ]. Moreover, it should be mentioned that tendon properties are strongly dependent not only on animal type but also on age, sex, site, feeding, living condition and general health status.…”
Section: Resultsmentioning
confidence: 99%
“…Very different values were registered compared to those found in literature, due to the different preconditioning and strain rates applied in this study from other literature [ 31 ]. Tendons had a viscoelastic behavior for which a strong test parameter dependence exists: an increase in the stress and strain at failure was registered with a strain rate increase [ 32 , 33 ]. Moreover, it should be mentioned that tendon properties are strongly dependent not only on animal type but also on age, sex, site, feeding, living condition and general health status.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown that the mechanical response of collagen fibrils in tendon to overload depends on both the enzymatic cross-link profile and the loading rate. While the collagen fibrils of tendons that contain less hydrothermally stable enzymatic cross-linking readily undergo discrete plasticity in response to overload (20,27,39), those with more hydrothermally stable cross-linking only undergo discrete plasticity when overloaded at slow loading rates (10). The impact that AGE cross-linking may have on the overload response of tendons with significant levels of trivalent cross-linking, typically seen in high stress tendons such as the human patellar (12) or Achilles (19), remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…For SEM, specimens are commonly sputter coated with gold palladium before imaging. For TEM, ultrathin sectioning, staining or contrasting are applied after embedment.…”
Section: Electron Microscopymentioning
confidence: 99%
“…After preconditioning, the loss of cohesion, integrity, and parallelism of the collagen fibrils was observed in the SEM images with a significant decrease in CIP scores. At higher magnification, Chambers et al . investigated the morphological change after tendon rupture, and the SEM images showed longitudinally distributed discrete kink‐type sites of plastic deformation and frequent loss of D‐banding in the extensor tendons, while the flexor tendons exhibited less damage.…”
Section: Electron Microscopymentioning
confidence: 99%